Los hábitos alimenticios y su relación con el aprendizaje de los niños y niñas del primer grado de educación general básica del centro de educación básica “Luz Victoria Rivera de Mora” del cantón Balsas provincia de El Oro, periódo 2014 – 2015”. Lineamientos propositivos - Hidalgo León, María Esther (2014)
The titled thesis "THE NUTRITIOUS HABITS AND THEIR RELATIONS IN BASIC GENERAL EDUCATION FIRST GRADE CHILDREN LEARNING "LUZ VICTORIA RIVERA DE MORA” SCHOOL OF BALSAS CANTON EL ORO PROVINCE; PERIOD 2014-2015". PROPOSITIONAL GUIDELINES. It I was structured following the investigation proposed by the Loja National University. The general objective that guided the investigative work was: To establish the incidence of the Nutritious Habits in the Basic General Education First Grade Children Learning "Luz Victoria Rivera de Mora” school of Balsas Canton El Oro province. The used methods were: Scientific, Inductive, Deductive, Analytic-synthetic and Statistical Model. The techniques were the following ones: The Survey applied the Parents of Family of High School, First Grade of Basic General Education of the School "Luz Victoria Rivera de Mora" to know the Nutritious Habits of the children to determine the Learning. In the implementation of the survey to teachers concluded that: 100% of children consume fruits and milk, 91% bread and pasta, 87% grain, 82% chicken, 55% meat, and 31 % vegetables, 27% fish, 18% vegetables, foods that provide their body with the nutrients needed for their age. Similarly, 91% of parents surveyed believe that in your family there are good Eating Habits that allow your son or daughter a balanced diet. According to the Observation Guide it was determined that: 69% of investigated children show a Very Satisfactory Learning; 21% Satisfactory; and 10% don’t very Satisfactory, for what you can determine that a low percentage of children that require to improve their Learning.